Low miR-936-mediated upregulation of Pim-3 drives sorafenib resistance in liver cancer through ferroptosis inhibition by activating the ANKRD18A/Src/NRF2 pathway - Li, Xiao; Cui, Mengna; Xu, Long; Guo, Qie (Frontiers in Oncology, 2024)
ObjectiveSorafenib, a multikinase inhibitor, is currently the standard treatment for advanced liver cancer. However, its application has become limited by the development of drug resistance. We intended to explore the mechanisms underlying the development of sorafenib resistance, therefore identifying an effective strategy to overcome sorafenib resistance remain challenges.MethodsHere, the follow-up of liver cancer patients undergoing sorafenib therapy, as well as animal tumor challenge and treatment were performed. The sorafenib-resistant liver cancer cell lines Huh7/SOR and HepG2/SOR were also established. miRNA and mRNA microarray analyses, TargetScan prediction, dual luciferase reporter assay, RNA pull-down assay, co-mmunoprecipitation (Co-IP) and pull-down assays, a transcription factor-specific NRF2 assay, an iron detection assay, a lipid peroxidation quantification assay, a ROS measurement assay, and GSH/GSSG and GSH-px standard quantitative assays were used.ResultsWe showed that upregulation of the provirus-integrating site for Moloney murine leukemia virus 3 (Pim-3) predicted poor response and unsatisfactory prognosis in sorafenib-treated liver cancer patients. Similarly, Pim-3 expression was positively associated with sorafenib resistance in liver cancer cells. Furthermore, microRNA-936 (miR-936) targeted the 3’-noncoding region (3'-UTR) of Pim-3 but exhibited lower expression in sorafenib-resistant liver cancer cells than in their parental cells. The high expression of Pim-3 mediated by miR-936 insufficiency activated the ANKRD18A/Src/NRF2 pathway which rearranged the expression of the indicated markers involved in iron distribution and lipid peroxidation homeostasis. MiR-936 overexpression and GV102-Pim-3-shRNA significantly attenuated the activity of the ANKRD18A/Src/NRF2 pathway to decrease the expression of Ankyrin repeat domain-containing protein 18A (ANKRD18A), Src, and Nuclear factor (erythroid-derived 2)-like 2 (NRF2), especially decreasing NRF2 nuclear retention and transcriptional activity. The transcriptional activity of NRF2 prompted cell ferroptosis because the transfection of miR-936 mimics, GV102-Pim-3-shRNA and GV102-NRF2-shRNA plasmid increased the expression of transferrin receptor 1 (TFR1) and divalent metal transporter 1 (DMT1) but decreased the expression of solute carrier family 7 member 11 (SLC7A11), glutathione peroxidase 4 (GPX4), quinone oxidoreductase 1 (NQO1), and heme oxygenase-1 (HO-1), thus facilitating the accumulation of intracellular Fe2+, lipid peroxides, and reactive oxygen species (ROS) but reducing the glutathione (GSH) level. Moreover, the elevated expression of Pim-3, resulting from the absence of miR-936 enhances sorafenib resistance in liver cancer by inhibiting cell ferroptosis.ConclusionPim-3 can be regarded as a target in the treatment of sorafenib-resistant liver cancer.